Biomimicry in architecture - Pawlyn, Michael (Newcastle upon Tyne : RIBA Publishing, 2016)
When searching for genuinely sustainable building design and technology - designs that go beyond conventional sustainability to be truly restorative - we often find that nature got there first. Over 3.5 billion years of natural history have evolved innumerable examples of forms, systems, and processes that can be applied to modern green design. Aimed at architects, urban designers and product designers, this new edition of 'Biomimicry in Architecture' looks to the natural world to achieve radical increases in resource efficiency. Packed with case studies predicting future trends, this edition also contains updated and expanded chapters on structures, materials, waste, water, thermal control and energy, as well as an all-new chapter on light. An amazing sourcebook of extraordinary design solutions, Biomimicry in Architecture is a must-read for anyone preparing for the challenges of building a sustainable and restorative future
How can we build more efficient structures? -- How will we manufacture materials? -- How will we create zero-waste systems? -- How will we manage water? -- How will we control our thermal environment? -- What can biology teach us about light? -- How will we power our buildings? -- Synthesis -- Conclusions: what does biomimicry mean for people?
Includes bibliographical references (pages 148-158) and index
Keywords: Organic architecture; Sustainable architecture; Architecture -- Environmental aspects; Biomimicry